PENGARUH SUBSURFACE CONSTRUCTED WETLANDS TERHADAP BOD, TSS dan pH PADA INSTALASI PENGOLAHAN AIR LIMBAH DOMESTIK - , indah susanti ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Constructed wetlands is a wastewater treatment system stunting the real wetlands. With a vegetation as the microorganism growth spot and at once as the filter and adsorbtion media to the polutan within the wastewater. In this research the constructed wetlands system consist a subsurface-free water surface type of constructed wetlands basin, Equisetum hyemale as the vegetation combined, soil and gravel as the media with 2:1 ratio. The basin constructed in 0,5 m width, 1,5 m length and 0,5 m depth. With coeffisien volumetric (kv) of BOD is 1,23 (day-1)